Analysis of Marketing Strategy Formulation in PT XYZ Using IFE, EFE, IE, and Space Methods - Kolose Saputra; Nanang Alamsyah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Corporate strategy is essential in dealing with global changes. PT XYZ is an international-scale company that requires the right strategy especially in marketing its products. Using the matrix analysis method IFE, EFE, IE, and SPACE by obtaining data based on interviews with one person who is influential in making decisions in the company, the company's internal factors and external factors that influence company performance are obtained. The results of this study are based on the IFE matrix the company has eight strength variables and two weakness variables, based on the EFE matrix the company has six opportunity variables and four threat variables, based on the IE matrix the company can take advantage of existing opportunities, and based on the SPACE matrix the company is in stable condition and has a role in the market.